A regional sahelian grassland model to be coupled with multispectral satellite data. I. Model description and validation - Mougin, E.; Seen, D. lo; Rumbal, S.; Gaston, A.; Hiernaux, Pierre H.Y. (Elsevier, 1995)
An approach to combining remote sensing spectral measurements with an ecosystem process model is presented. In this approach, the ecosystem model is not bound by the sole use of satellite data, but integrates the latter in an explicit formulation of the main processes of vegetation functioning. A close analysis of the relationships between processes described by the model and spectral measurements can therfore be carried out, and the capability of the model to be driven by remote sensing can also be investigated. This first article presents a regional ecosystem process model for Sahelian regions. The model describes a herbaceous layer composed of only annual species. The process of the soil-plant-atmosphere system, such as water fluxes in the soil, evaporation, transpiration, photosynthesis, respiration, senescence, litter production, and litter decomposition at the soil surface, are modeled. Moreover, structural parameters such as vegetation cover fraction, LAI, and canopy height, which are essential parameters for coupling with physical models of reflectivity, are also simulated. Comparison with aboveground biomass measured between 1976 and 1992 at a regional scale in two different regions of the Sahel, namely, Ferlo in Senegal and Gourma in Mali, shows that the model is able to simulate the temporal evolution of the aboveground biomass components.